Evaluation of Social Assistance Programs During the COVID-19 Pandemic: Helping or Giving Addiction to the Public - Haimah, Haimah; Nuphanudin, Nuphanudin; Setyowati, Eni; Khair, Otti Ilham; Alamsyah, Alamsyah (HK-Publishing, 2022)
AbstractThe emergence of a pandemic caused a lot of difficulties faced by the community to survive. This caused the government to intervene and provide various assistance to the community. However, there are often problems in the process of providing this assistance. This study aims to evaluate social assistance provided by the government to the community. This research will be conducted utilizing a qualitative methodology. This study utilized secondary data acquired from still-relevant research or previous investigations. This study found that there was the use of incomplete data and confusing regulations, so social assistance was abused. Some people have jobs and decide to register on the pre-employment card. Then some people are economically capable but do not report themselves so that later they can still get social assistance from the government again.Keywords: Social Assistance, Abuse, Community, Government.Â AbstrakMunculnya pandemi menyebabkan banyak kesulitan yang dihadapi masyarakat untuk bertahan hidup. Hal ini menyebabkan pemerintah turun tangan dan memberikan berbagai bantuan kepada masyarakat. Namun, seringkali ada kendala dalam proses pemberian bantuan ini. Penelitian ini bertujuan untuk mengevaluasi bantuan sosial yang diberikan oleh pemerintah kepada masyarakat. Penelitian ini akan dilakukan dengan menggunakan metodologi kualitatif. Penelitian ini menggunakan data sekunder yang diperoleh dari penelitian yang masih relevan atau penyelidikan sebelumnya. Penelitian ini menemukan adanya penggunaan data yang tidak lengkap dan peraturan yang membingungkan sehingga bansos disalahgunakan. Beberapa orang memiliki pekerjaan dan memutuskan untuk mendaftar di kartu prakerja. Kemudian sebagian masyarakat yang mampu secara ekonomi tetapi tidak melapor agar nantinya masih bisa mendapatkan bantuan sosial dari pemerintah lagi.Kata kunci: Bansos, Penyalahgunaan, Masyarakat, Pemerintah.